The effect of CYP1A2 gene polymorphisms on caffeine pharmacokinetics and exercise performance in male recreational athletes - Masters C; Ali A; Badenhorst C; Dickens M; Rutherfurd-Markwick K (Wiley, 2026)
This study examined the effects of caffeine consumption on endurance exercise performance, and the influence of CYP1A2 gene polymorphisms in caffeine pharmacokinetics and exercise performance. The data sets of two randomised, double blind, placebo-controlled crossover study design experiments have been merged. Thirty-eight recreationally active male participants provided saliva samples for CYP1A2 genotyping (AA homozygotes n = 19; AC heterozygotes n = 19) and completed either a 10-km run or 40-km cycling time trial of 60-min following a single dose of 6 mg·kg-1 caffeine (CAF) or placebo (maltodextrin; PLA) throughout which heart rate (HR) and time to completion (TTC) were measured. Caffeine ingestion improved TTC by 1.8% (p = 0.05; ηp 2 = 0.12). HR was higher in CAF trials compared to PLA (p = 0.02; ηp 2 = 0.15). Plasma caffeine concentrations were higher in AA allele carriers compared with AC allele carriers (p = 0.04; ηp 2 = 0.139). No caffeine-gene interaction effects were observed in TTC, HR or plasma concentrations of paraxanthine and theophylline. Total caffeine plasma concentrations in the area under the concentration-time curve (AUC) were significantly higher in AA allele carriers compared with AC allele carriers (p = 0.01). Ingesting a dose of 6 mg·kg-1 caffeine 60-min prior to exercise is likely to improve performance in endurance activities in recreationally trained males. Plasma caffeine concentrations were significantly higher in AA allele carriers compared to AC allele carriers, though no gene-caffeine interaction main effects were observed in TTC; so, the role of CYP1A2 gene polymorphisms in determining enhancements in exercise performance remains unclear.
Keywords: athlete; endurance exercise; genetics; physical activity; sport; Humans; Caffeine; Male; Cytochrome P-450 CYP1A2; Cross-Over Studies; Double-Blind Method; Polymorphism, Genetic; Athletic Performance; Young Adult; Adult; Heart Rate; Physical Endurance; Athletes; Genotype; Theophylline; Running